Antibacterial properties of carvacrol against antibiotic-resistant bacteria, enteric bacteria, and oral pathogens - Hoş, Ayşegül; Omurtag Özgen, Pınar Sinem; İnci, Ayşe; Avcı, Buse; Ceylan, Ceyda (Marmara University, 2023)
The present study investigated the antibacterial activity of carvacrol against Vancomycin-Resistant Enterococci (VRE), Carbapenem-Resistant Enterobacteriaceae (CRE), Methicillin-Resistant Staphylococcus aureus (MRSA), Escherichia coli ATCC 8739, Enterococcus faecalis ATCC 29212, Streptococcus mitis, Streptococcus mutans CNCTC 8/77 and Streptococcus salivarius CNCTC 64/59. According to the results of the disc diffusion method, carvacrol has extremely high antibacterial activity with zones of 28 mm, 38 mm, 39 mm, 36 mm, 50 mm, 41 mm, 47 mm, and 39 mm against E. coli, E. faecalis, VRE, CRE, S. salivarius, S. mutans, MRSA, S. mitis, respectively. In the present study, the Minimum Inhibition Concentration (MIC) was also investigated by using the Broth Microdilution method. Carvacrol has MIC of 7.62 mg/mL against E. coli, 15.25 mg/mL against VRE, 30.5 mg/mL against E. faecalis, CRE, and S. salivarius, 61 mg/mL against S. mutans, 1.90 mg/mL against MRSA and S. mitis. Carvacrol is a very strong antimicrobial agent and may be used in important applications in the food and pharmaceutical industry. It may also be a good candidate for developing alternative treatments. The results of the present study may be beneficial for further studies with this antibacterial agent for both academia and industry.
Keywords: Antibacterial Activity; Antibiotic Resistant Bacteria; Carvacrol; Enteric Bacteria; Oral Pathogens